A VALUE-BASED IPS LEARNING STRATEGY TO DEVELOP STUDENTS' PHILANTHROPICAL ATTITUDES AND SOCIAL CONCERN - Ponidi; Akrim; Amini (Academic Solution Publisher, 2026)
This study aims to describe and analyze the strategies used by Social Studies (IPS) teachers in integrating humanistic values to foster students' philanthropy and social concern. The challenges of modernity and individualism in the digital era demand a repositioning of Social Studies learning, shifting it from merely a transfer of knowledge to a transfer of value. This study employed a descriptive qualitative approach. Data collection was conducted through in-depth interviews with Social Studies teachers, observation of learning activities, and documentation of school social programs. Data analysis applied the Miles and Huberman model, which encompasses data reduction, data display, and conclusion drawing. The results of the study indicate that effective Social Studies teacher strategies include: (1) infusing humanistic values into contextual teaching materials, (2) implementing the Problem-Based Learning (PBL) model related to real social issues, and (3) habituating philanthropic actions through school social programs. Through these integrated strategies, students not only understand spatial and social concepts cognitively but also internalize them in the form of sharing awareness (philanthropy) and sensitivity to the suffering of others in their daily lives.